P1088Effect of coronary artery disease on patients with atrial fibrillation and heart failure with preserved ejection fraction - from vicious twins to vicious triplets?. (18th June 2020) - Stephan, T; Kuehberger, A; Baumhardt, M; Weinmann, K; Felbel, D; Bothner, C; Pott, A; Dahme, T; Rattka, M
Abstract: Background: Atrial fibrillation (AF) and heart failure with preserved ejection fraction (HFpEF) are common diseases and associated with increased morbidity and mortality, which even aggravates if both conditions are coexisting. Coronary artery disease (CAD) is highly prevalent in both, patients with AF (17-46%) and HFpEF (50-80%). Notably, all three entities share several common risk factors. While it is well established that the emergence of the vicious twins HFpEF and AF is mechanistically linked, CAD can also be pathophysiological related to HFpEF, as well as AF by several mechanisms. Aim: The study aimed to evaluate the influence of CAD on patients with concomitant AF and HFpEF and to identify parameters affecting the patients clinical outcome. Methods: We retrospectively screened patients with AF and HFpEF for CAD. Patients with and without CAD were compared by relevant patient characteristics and echocardiographic parameters at baseline and at the end of follow-up. Additionally, we assessed hospitalization rates and  performed multivariate logistic regression to analyze parameters influencing the clinical outcome.  Results: Between January 2013 and December 2016 6.114 patients with atrial fibrillation and 2.187 patients with echocardiographic diastolic dysfunction were treated at our university hospital department. Of those, 127 patients had concomitant diagnosis of HFpEF according to current guidelines and AF. In 77 patients (61%) CAD had been diagnosed by coronary angiography. At baseline, CAD patients had significantly more myocardial infarction, dyslipidemia, use of aspirin, lower left ventricular ejection fraction, larger left ventricular diastolic diameter and a higher CHA2DS2-VAsc score. Moreover, CAD patients had significantly higher rates of all-cause and cardiovascular hospitalizations. Interestingly, NYHA-class and left ventricular mass index improved significantly in the group without CAD, whereas there was no change in the CAD-group. Multivariate logistic regression only associated catheter ablation for AF significantly with NYHA improvement in the total cohort. Assessment of all-cause and cardiovascular hospitalization in CAD patients undergoing either catheter ablation or medical therapy revealed, that catheter ablation significantly decreased event rates. Moreover, catheter ablation for AF was associated with echocardiographic signs of reverse remodelling, whereas conservative treatment resulted in progression of remodelling.  Conclusion: This is the first study to evaluate the effect of CAD on patients with concomitant AF and HFpEF. As expected, presence of CAD was related to a worse clinical outcome. Interestingly, in CAD patients catheter ablation was significantly associated with functional and clinical improvement. In conclusion, catheter ablation for AF might display an effective therapeutic approach in this vulnerable population.